A priority supposition for estimation of time‐dependent changes in thickness and weight of polymeric flat sheet membranes fabricated by the nonsolvent induced phase separation (NIPS) technique. Issue 6 (22nd June 2017) - Asgarpour Khansary, Milad; Aroon, Mohammad Ali; Marjani, Azam; Shirazian, Saeed
Abstract: During the fabrication procedure of polymeric membranes using nonsolvent induced phase inversion technique, thickness and weight of the polymeric cast film change rapidly. The only available guideline just presents a qualitative criterion for thickness change in which "penetration of the denser species into the film and the elimination of the lighter ones from film to coagulation bath" have been related to the densification of the cast solution and its thickness reduction. While it is well‐suited for cellulose acetate/acetone/water ternary system, it is not applicable to our investigated systems, that is, polyethersulfone/n‐methyl‐pyrolidine/water and polysulfone/N‐methylpyrrolidone/water. Thus, here the thermo‐kinetic behavior of NIPS process was discussed, and then a thermodynamic model was developed, in which only initial cast film and final membrane properties were used as inputs. Two new simple suppositions were derived and examined. The use of thermodynamic modeling approach results in desirable estimation of overall changes, and the proposed suppositions also can be reliably used for prediction of changes in mass and thickness experienced by cast film NIPS process. It was shown that without the implication of some serious assumptions, it is impossible to derive the old supposition from theoretical concepts. It was also found that the interpretation of film thickness reduction in literatures cannot be validated. Using the presented theoretical concept, one can obtain an overview of the decrease and/or increase in thickness and/or weight of final fabricated membrane prior to any experimental investigation.